Causes of fall of Rome - Alexander, Kate (My University, 1906)
Introduction: Though 476 A.D. is the date recognized by historians, as the date of the downfall of Rome, it is not to be considered as arbitrary. The forces that undermined that great power, which had dominated the civilized world for centuries, had been constantly at work since the Antonines; and even before, for was not the mere fact of the change in the form of government, from a republic to a monarchy, significant of a decline? It is conceded by historians that in many respects the accession of the Caesars was a decided benefit, though it undeniably was an unwarranted usurpation of power; and if the Romans of that time had possessed the virtues and intellectual qualities of their forefathers, would they not have clung tenaciously to their old liberties, and have yielded them up only after a desperate struggle? Though the decline in character was evident before, the decline in power was first noticeable in the second century of the Empire, during the reign of Marcus Aurelius. While he was one of the best of the Emperors, he had difficulty in maintaining the frontiers against the Germans, thus disclosing the weakness of that once invincible organization, the Roman army. Commodus, the much indulged son of Marcus Aurelius, brought disgrace upon the name of the Antonines.
Citation: Alexander, Kate. Causes of fall of Rome. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Roman Empire; Fall of Rome; History; Theses; Manuscripts (documents)